Perilaku Rusuh Mahasiswa Mappi di Yogyakarta - Ismail Takan; Antonius Ian Bayu Setiawan (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
The discussion of this study is related to the factors causing aggressive behavior that is dominant in Mappi students. This study aims: (1) to determine the factors causing riotous (aggressive) behavior (2) to determine the types of riotous behavior possessed by Mappi students in Yogyakarta.This type of research uses a qualitative descriptive case study. This research was conducted at the Sanata Dharma University Student Dormitory, Jl. Jenengan Raya, Maguwoharjo, Depok District, Sleman Regency, Yogyakarta. The implementation of this research was from December 22 to January 17, 2024. The subjects of this study were 5 people, consisting of 4 employees of the Sanata Dharma University Student Dormitory and 1 shop owner. Data collection techniques used interviews, data analysis techniques managed and prepared data, read all data. Analyze by coding data, apply the coding process to describe the things to be analyzed.Results: There were 4 causes of the riots, namely: differences in stance, culture, affairs, community values. There are 4 types of behavior, namely: hate, achieving goals, spontaneous, revenge. Conclusion: Aggressive behavior of Mappi students is caused by unhealthy friendships and genetic factors. The type of behavior of Mappi students is closed social behavior.